Technical and locomotor demands in elite soccer: manipulating area per player during small-sided games to replicate official match demands - Riboli, A.; Esposito, F.; Coratella, G. (Biology of Sport, 2023)
The present study aimed to investigate the area per player (ApP) to replicate the technical and locomotor match demands using small-sided games (SSGs) in male soccer players (n = 20) competing in major European and UEFA competitions. The relative number of each individual technical activity per minute (number · min-1; technical demands) was counted and the relative (m · min-1) total (TD), high-speed running (HSRD), very high-speed running (VHSRD), sprint and acceleration+deceleration (Acc+Dec) distances were collected during different SSG formats (n = 24; 4 vs 4 to 10 vs 10 with an ApP from 60 to 341 m2 · player-1) and official matches (n = 28). Data were collected during two full seasons. A linear mixed model analysis was used to calculate the individual relationship between technical/locomotor demands and the ApP during SSGs; the correlation coefficient was also calculated. With the exception of an inverse moderate (r = -0.457) correlation for Acc+Dec, each locomotor metric (TD, HSRD, VHSRD and sprint) showed a positive large to very large (r = 0.560 to 0.710) correlation with ApP (P < 0.001). The technical demands showed an inverse moderate correlation (r = -0.529) with ApP. Additionally, inverse moderate to large correlations (r = -0.397 to -0.600;P < 0.05) between the technical demands and the locomotor demands (TD, HSR, VHSR and sprint) were found. Lastly, an ApP of ~243 m2 · player was found to replicate the official match technical demand and it was quite similar to the ApP required to replicate HSRD, VHSRD and sprint. These findings may help practitioners to replicate, overload and underload both technical and locomotor demands using a specific ApP during SSGs in elite soccer.